Pengaruh Ukuran Partikel Kulit Lengkeng (Dimocarpus longan) yang Termodifikasi CTAB Terhadap Adsorpsi Ion Logam Pb(II) - Putri Rinjani, Mitna Sekar; Kurniawati, Desy; Alizar, Alizar; Sari, Trisna Kumala (Departemen Kimia FMIPA UNP, 2025)
Study This aiming For analyze material characteristics using Spectroscopy Infrared Fourier Transform (FT-IR) and measure size particle . The FT-IR method is used For identify group function And component chemistry in sample , while analysis size particle done For determine distribution And morphology particle . Objective study This is For increase efficiency adsorption through modification surface biosorbent using CTAB. FT-IR results show existence peaks spectrum indicating existence bond chemistry certain , which provides outlook about material structure . Capacity maximum obtained at pH 6, concentration 250 ppm, time 60 minutes contact , and size 180 µm particles . research This show that peel modified longan with CTAB having potential tall For used as biosorbent effective in processing waste metal heavy.